Opening doors in Latin America (The Board, 1914)
The key to the Guatemalan situation / Paul Burgess.--"In peril from the heathen" / Florence E. Smith.--Pioneers in a great land / H.P. Midkiff.--The Mexican minister and the Protestant opportunity / Charles Petran.